Pharmacoeconomic analysis of anti-angiogenic therapy for diabetic macular edema - S. V. Nedogoda; I. N. Barykina; A. S. Salasyuk; V. O. Smirnova; E. A. Popova (Izdatelstvo OKI, 2019)
Te purpose of the study is to assess the economic consequences of the use of various anti-VEGF drugs in patients with diabetic macular edema (DME).Materials and methods. Te cost-eﬀectiveness analysis and budget impact analysis was conducted from the payer perspective (health insurance system).Results. In accordance to the results from RCT (Protocol T) aﬂibercept required a lower number of intravitreal injections (IVI) and laser coagulations for frst year and it has tendency for lower number of IVI for the second year of treatment that resulted in lower costs for aﬂibercept therapy by 122,819 rubles (12.7 %) per patient within frst 2 years (1st year - 66,632 rubles, 2nd year - 61,186 rubles) in comparison with ranibizumab. Te cost-eﬀectiveness analysis showed that aﬂibercept is a "cost-eﬀective" method of treating patients with DME compared to ranibizumab in Pro Re Nata (PRN) mode. Te budget impact analysis has shown savings for the health insurance system (12 million rubles) for the analyzed patient cohort (n = 100) with aﬂibercept in 2 years (1st year - 6.163 million rubles; 2nd year - 6.119 million rubles). Te analysis of "lost opportunities" in a cohort of 100 patients showed that the use of aﬂibercept in DME can free up to 216 hospitalizations within 2 years (109 cases in the 1st year and 107 in the 2nd year). As a result, about 14 patients with DME can be additionally treated with aﬂibercept for two years within a fxed budget.Conclusion. Treatment of DME with aﬂibercept can save resources of health insurance system compared to use of ranibizumab.